NON-FORMAL EDUCATION IN THE SYSTEM OF EDUCATION OF UKRAINE - Pavlyk, Nadiia P. (Educological discourse, 2016)
The characteristics of a modern system of education in Ukraine from the view of sociology of education; system approach and theory of pedagogical innovations are presented in this article. Social importance of education, its social and individual results is outlined. Institutionalization of education as the hierarchical educational activity is described. The features of education as a social institution are defined. The structure of education as an open system of pedagogical subsystems different in types, degrees, levels, links is described. The law of continuity of education that has led to the development of its non-formal and informal forms is characterized. Social background of the development of theory and practice of organization of non-formal education as non-institutional, purposeful, volunteer activity of public associations and centers in the field of education is defined. The groups of individuals of non-formal education are determined.